Curbing Hate Speech through Education: Modalities for Equipping Future Teachers - Philip, Rosamma (Journal of Pedagogy and Education Science, 2023)
A holistic education that embraces children's physical, emotional, intellectual, and social growth within a framework of human values is essential for the sustainable development of humanity. Inappropriate use of language causes intolerance, violence and disharmony in society. Training for the effective use of peaceful language through education is a vital need of the present community. Hate speech, verbally and digitally, has become one of the most common methods for spreading disruptive and discriminatory messages and ideologies. Education has a significant role in curbing hate speech and equipping learners to combat hate speech and intolerance. Educational practices that promote respect for pluralism and diversity in all areas of life are to be framed at the teacher education level to equip prospective teachers to face the challenges of hate speech. This paper presents the definition, cause and consequences of hate speech in an educational context and proposes strategies to empower future teachers to address hate speech. Prospective teachers are to be trained to address the issues of hate speech through various methods, as suggested in the paper.